THE DEVELOPMENT OF DOMESTIC AUTOMOTIVE INDUSTRY: THE ROLE OF INDONESIAN GOVERNMENT TO COMPETE THE JAPANESE AUTOMOTIVE INDUSTRY - Rizqi Candra Adi Nugroho Nugroho (Mediasi: Journal of International Relation)
Abstract This research will explain the roles carried out by the Indonesian government in developing its domestic automotive industry to compete the Japanese automotive industries. This research will focus on two policies namely protection policies and cooperation policies implemented by the Indonesian government. This study used qualitative research methods, by having data collection technique in the form of books, journals, and data obtained from reliable website pages and can be used in research. The results of this study explained that the roles of the government were not been effective in developing the domestic automotive industry. This was because there were two conflicting policies, namely protection policies and cooperation policies with Japan. This was caused by several free trade agreements that were established by Indonesia and foreign countries, one of which is Japan and regulates taxation and import duties on motorized vehicles, will not be affected by the protection policies implemented by the government. This led to an increase in the dominance of Japanese automotive products in the Indonesian market accompanied by a reducing the roles of the national automotive industry which resulted in a smaller opportunity for Indonesia to establish an independent automotive industry. Keywords: Indonesia, Japan, Automotive, Protection Policy, Cooperation Policy.